2013
DOI: 10.1103/physreve.87.032715
|View full text |Cite
|
Sign up to set email alerts
|

Flexoelectricity and thermal fluctuations of lipid bilayer membranes: Renormalization of flexoelectric, dielectric, and elastic properties

Abstract: Thermal fluctuations renormalize the bending elasticity of lipid bilayers. This well-studied effect is a cornerstone in the study of several membrane biophysical phenomena. Analogously, nearly all membranes are endowed with an electromechanical coupling called flexoelectricity that admits membrane polarization due to curvature changes. Flexoelectricity is found to be important in a number of biological functions including hearing, ion transport and in some situations where mechanotransduction is necessary. Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Given the absence of any plausible micromechanism for piezoelectricity, flexoelectricity is most likely the key mechanism underpinning the electromechanical coupling in biomembranes. It has been found to be relevant for studying ion channels, thermal fluctuations, equilibrium shape of the vesicle, and electromotility [26,[42][43][44][45][46][47]. Based on several hypotheses and experiments [48][49][50][51][52][53][54][55], the mammalian hearing mechanism appears to be one of the most exciting implications of flexoelectricity in biology.…”
Section: What Is the Role Of Flexoelectricity In Biology?mentioning
confidence: 99%
“…Given the absence of any plausible micromechanism for piezoelectricity, flexoelectricity is most likely the key mechanism underpinning the electromechanical coupling in biomembranes. It has been found to be relevant for studying ion channels, thermal fluctuations, equilibrium shape of the vesicle, and electromotility [26,[42][43][44][45][46][47]. Based on several hypotheses and experiments [48][49][50][51][52][53][54][55], the mammalian hearing mechanism appears to be one of the most exciting implications of flexoelectricity in biology.…”
Section: What Is the Role Of Flexoelectricity In Biology?mentioning
confidence: 99%
“…As is well-known, thermal fluctuations cause softening of membrane mechanical properties e.g. [63]. Decrease in stretch modulus will increase the deformation and hence likely increase the sensitivity of the magnetic to electric conversion.…”
Section: Ellipsoidal Shape and Dimensions Changementioning
confidence: 99%
“…Reversibly, a substantially large external electric field across the membrane may also redistribute and reorientate these molecules due to electrical attraction and repulsion, resulting in a change in the membrane surface curvature: the reverse flexoelectric effect. Flexoelectricity is found to play a significant role in a number of biological functions, such as ion channels, thermal fluctuation, vesicle equilibrium, and hearing functions [10,29,[36][37][38][39][40]. In neurons in particular, it has been suggested that both the above-mentioned membrane movement during AP propagation, as well as the membrane polarization during an AP, could be related to the flexoelectricity [36,41].…”
Section: Introductionmentioning
confidence: 99%